Selective sensing of hydroquinone and catechol based on multiwalled carbon nanotubes/polydopamine/gold nanoparticles composites - Wang, Yong; Xiong, Yingying; Qu, Jianying; Qu, Jianhang; Li, Shufang (Sensors and actuators. B, Chemical, 2016)
•Multiwalled carbon nanotubes/polydopamine/gold nanoparticles composite (MWCNTs/PDA/AuNPs) was synthetized successfully.•A novel electrochemical sensor for simultaneous determination of hydroquinone and catechol based on MWCNTs/PDA/AuNPs and chitosan was developed.•The peak potential of the oxidation peaks of HQ and CC were at 192mV and 297mV, respectively, indicating an anodic ΔEp of 105mV, which is wide enough to separate the two components.•The sensor showed wide linear responses for HQ and CC with detection limits of 35nM and 47nM, respectively. In this work, a highly sensitive and selective electrochemical sensor based on multiwalled carbon nanotubes/polydopamine/gold nanoparticles composites (MWCNTs/PDA/AuNPs) and chitosan (CS) was developed, which was used for simultaneous determination of hydroquinone (HQ) and catechol (CC) derived from a large specific area of MWCNTs and superexcellent electroconductibility of AuNPs. It was found that HQ and CC could be completely separated on the electrode using cyclic voltammetry and differential pulse voltammetry technique under optimal conditions. The proposed sensor based on MWCNTs/PDA/AuNPs exhibited linear responses for HQ and CC from 0.1 to 10μmolL−1 with detection limits (S/N=3) of 0.035μmolL−1 and 0.047μmolL−1, respectively. In addition, the modified electrode was successfully implemented in the simultaneous determination of CC and HQ in tap and lake water samples. And compared with other methods, this sensor exhibited good sensitivity, stability and reproducibility.